Officers and Staff of AIME (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1961)
[Admissions: H. J. Gruy, Chairman Kenneth W. Robbins W. Frank West Aurel E. Smith R. F. Madera Tom G. Calhoun Kenneth F. Anderson B. M. Goltlieb Advertising: Clark R. Edgecomb, Chairman Bernard F. Klein. Henry N. Lyle R. E. Howard H. M. Krause, Jr. Education: R. L. Whiting, Chairman John M. -Campbell E. T. Guerrero Don D. Little J. C. McCarthy Frank G. Miller Douglas Ragland H. C. Slider R. L. Slobod]